Differential pressure control method for pharmaceutical cleanrooms under variable air supply conditions. (1st April 2022) - Cheng, Xuanrui; Li, Chunwang; Ma, Xiaojun; Shao, Xiaoliang
Abstract: Existing methods for maintaining pressure gradient in a pharmaceutical cleanroom rely on the condition of steady air supply. When the air supply volume in a cleanroom changes considerably from one state to another, the pressure gradient inside the cleanroom becomes turbulent, reducing the robustness associated with the existing methods. Therefore, a variable residual air volume tracking method is proposed in this paper to maintain the pressure gradient in a multi-compartment cleanroom under variable air volume conditions. By establishing a data relationship model between the cleanroom air supply volume (or damper opening degree) and residual air volume compensation coefficient, a fixed leakage air volume is maintained in the cleanroom under a given pressure gradient. Furthermore, the air volume inside the cleanroom and the residual air volume are adjusted in real-time. The balancing of return air volume overcomes various errors and interferences in the system, to achieve pressure gradient stability under variable air volume. Experimental results show that when the air supply volume changes within ±10%, the pressure amplitude change in each room with the proposed method is significantly reduced compared with usage of the traditional fixed residual air volume method. The study could guide the comprehensive maintenance of differential pressure inside cleanrooms. Highlights: Variable residual air volume tracking method for pharmaceutical cleanrooms. Data relationship model with air supply volume and residual air volume compensation coefficient. A fixed leakage air volume is maintained under a given pressure gradient. Room air supply volume and residual air volume in cleanrooms are maintained in real-time. Pressure gradient is controlled under variable air supply volume for pressure gradient stability.